Effect of performance speed on the kinematics and kinetics of two trunk and hip strengthening exercises - Elvira, J. L. L.; Barbado, D.; Flores-Parodi, B.; Vera-Garcia, F. J. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The aim of this work was to study the effect of speed on the sit-up (SU) and leg raising-lowering (LRL) exercise technique. Seventeen subjects volunteered to participate, performing at 3 cadences. Video 3D analysis was conducted and ground reaction forces were record. The anterior-posterior displacement of the centre of pressure (COP) and mean range of motion (ROM) for 6 angles were calculated. Results indicate that when SU speed increases, hip and knee ROM increase, while there is a decrease in the upper trunk flexion. In the LRL there is a decrease in the pelvic tilt and hip angle, and an increase in the knee angle. It seems that in higher speed exercises, subjects modified their technique to keep up with the cadence. Coaches and trainers should control the subjects' technique during the execution of these high speed exercises.